Potential environmental pressures on water availability in Gembong reservoir in Pati District for the development of agropolitan area. (May 2019) - Kartono; Purwanto; Suripin
Abstract: Land-use management is the key parameter in developing an agropolitan area. The Spatial Plan of Pati District 2010-2030 contains plans for the Gembong Subdistrict to be developed into an agropolitan area. The Gembong Reservoir is one of the reservoirs in the region that has a vital role in supporting the area development. The main problem in managing the Gembong reservoir is the decreasing availability of reservoir water. Increased sedimentation affects the availability of reservoir water, which is used as a supply of irrigation areas. Management of water availability must be based on optimization analysis, because the volume of storage is limited and increasing inflow to the reservoir to increase the water level requires a long time. Therefore, the optimization model of reservoir water management is urgent to be formulated, so that the reservoir operator can be utilized to determine the allocation of supplementary water. This article presents a study of the results of observations in the field and secondary data, as well as reviews of related scientific articles, to be able to identify potential environmental stresses on reservoir water availability and its management.